JOURNAL OF GOVERNMENT & POLITICS : Technology, Emotion and Democracy: Understanding The Dunamic Through Abalyzing Conversation in Twitter - Indro Adinugroho , Smita Sjahputri (FISIPOL UMY, 2017)
Innovation in technology brings tremendous impact in various areas, including the issues of democracy, politics and government.